Strategies for Developing Millennial Farmers to Support Food Security - Munajat Munajat; Fifian Permata Sari; Yunita Sari (Goodwood Publishing, 2025)
Purpose: This study aims to identify key factors affecting millennial farmer’s human resource development and to formulate a strategic development approach using SWOT and Grand Strategy analyses to support food security in Ogan Komering Ulu Regency. Research Methodology: This study employs a mixed methods approach with an explanatory sequential design. Quantitative data were collected through a survey of 94 millennial farmers aged 19–39 years, while qualitative data were obtained through in-depth interviews supported by a SWOT analysis. Quantitative analysis was conducted using multiple linear regression, while strategy formulation applied the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT Matrix, and Grand Strategy Matrix. Results: The findings show that formal education, age, access to financing, agricultural extension services, and family support significantly influence millennial farmers’ human resource development, with an explanatory power of 86%. The SWOT and Grand Strategy analyses place the development strategy in Quadrant I (S-O), indicating a progressive and growth-oriented approach emphasizing digital agriculture training, agripreneurship development, digital markets, and institutional collaboration. Conclusions: Millennial farmers in the OKU Regency have good potential to support food security but require stronger digital skills and technology adoption. An aggressive strategy focusing on digital agriculture, financing access, and institutional collaboration is recommended for the future. Limitations: The study is limited by its regional scope and relatively small sample size, which may limit the generalizability of the findings. Contributions: This study provides strategic and empirical insights for policymakers, extension services, and research on developing millennial farmers to strengthen regional food security.